KONSEP QURROTA A’YUN SEBAGAI KARAKTER ANAK (STUDI AL-QUR’AN SURAT AL-FURQAN: 74 DAN AL-SAJDAH: 17) - Siti Maryam (stit-islamic-village, 2019)
Lately, many parents and educators are still complaining about the success of children's character education, especially in adolescence. Teenagers usually tend to violate moral values, ethics, and religious norms such as: undisciplined, not independent, disrespectful, against parents, lazy to learn, leave prayer, violence, fighting, brawls, etc. other. This creates a problem for parties: the government, schools, the community, more specifically for parents. Therefore research on the concept of qurrota a'yun as a child character based on the study of the Qur'an al-Furqan: 74, and as-Sajdah: 17 is important. There are various opinions of the scholars about the concept of qurrota a'yun, namely Ahmad Mustafa al-Maraghi, Ibn Kathir Muhammad Nasib ar-Rifa'i, Buya Hamka, and Quraish Shibab. The basic concept of child character education is religious, biological, psychological, sociological. So too, the role of parents and educators in shaping children's character can be done through a religious approach, habituation, emotional, rational, functional and obedience approach.